Análise acerca da necessidade de ampliação da licença-paternidade como instrumento de igualdade de gênero e de deveres parentais - PEREIRA, Estéfani Ivelin Leão (2024)
This monograph aims to analyze the need to expand paternity leave, highlighting that the limited amount of time currently granted to fathers perpetuates gender inequality, both in the distribution of parental responsibilities and in the job market. The problematization focuses on the discrepancy between the periods of paternity leave and maternity leave, highlighting that, although the 2002 Civil Code does not differentiate between paternal and maternal obligations, the practical reality demonstrates an overload on women. The methodology adopted is exploratory, combining bibliographical research with analysis of the relevant legislation and the Direct Action of Unconstitutionality by Omission nº 20. This approach seeks to establish a connection between doctrine, academic production and laws related to the topic. Therefore, it is concluded that the disparity in terms between licenses violates fundamental constitutional principles and goes against the contemporary conception of the family institute. Equalization of licenses is presented as a crucial measure to promote effective gender equality.